Pengaruh Pendekatan Inquiry Untuk Meningkatkan Kemampuan Berpikir Kritis Pada Siswa Sekolah Dasar - Sabila, Diah; Widiyono, Aan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
The research was carried out to answer problems found from the results of a preliminary study carried out by researchers when conducting observations at SDN 02 Tedunan. A problem was found, namely that in this learning process it would cause students to become less active and there were no student activities that really made a difference. The aim of this research was to see whether or not there was any influence of inquiry approach on improving the critical thinking skills of Class IV students of SDN 2 Tedunan. This research is classified as experimental research which uses quasi-experimental methods, one group pre-test and post-test design. The entire class IV of SDN 02 Teduhan is the population in this study. Data was collected through critical thinking ability tests. Based on this research, the results obtained from hypothesis testing are tcount of 10.648 and ttable of 1.729 because tcount 10.648 > ttable 1.729, so that Ho can be accepted and Ha is rejected,, that there is an influence of the inquiry approach to improve critical thinking skills in class IV students at SDN 2 Tedunan.